Polymer-based composite material containing multi-stage MOFs stress dissipation layer and preparation method and application of polymer-based composite material
By introducing MOFs materials such as MXene and Ni-BDC into polymer-based composite materials and building a multi-stage friction stress dissipation layer, the problems of insufficient toughness and easy wear in friction environments are solved, and excellent friction reduction and anti-wear properties and long-term stability are achieved.
Patent Information
- Application Number
- CN202411942429.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-27
AI Technical Summary
Traditional polymer-based composites have problems such as insufficient toughness, easy wear, uneven stress distribution and insufficient performance of traditional fillers in long-term use, especially in frictional environments, which are difficult to effectively disperse stress and energy.
By introducing MOFs materials such as MXene and Ni-BDC, and building a multi-stage friction stress dissipation layer, combining the hydrolysis reaction of ZIF-8 nanoparticles and PVA aqueous solution, a composite material with a volcanic-like structure was formed.
It significantly improves the friction-reduction and wear resistance, toughness and durability of composite materials, reduces the friction coefficient and wear rate, and extends the service life.
Smart Images

Figure CN119684734A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lubricating materials, and in particular to a polymer-based composite material containing a multi-level MOFs stress dissipation layer, and a preparation method and application thereof. Background Art
[0002] With the continuous development of materials science and engineering technology, polymer-based composites play an increasingly important role in industrial applications. However, common polymer-based composites still face the following problems: (1) Low toughness and easy wear: Traditional polymer-based composites usually have the disadvantages of insufficient toughness and easy wear. Especially in the long-term use process, friction and wear will cause surface damage of the material, thus affecting its service life and stability; (2) Uneven stress distribution: The dispersion of fillers in the polymer matrix has an important influence on the tribological and mechanical properties of the material. Uneven filler distribution will lead to local stress concentration, which will accelerate wear; (3) Insufficient traditional fillers: Common tribological performance enhancing materials (such as graphite, carbon nanotubes, inorganic fillers, etc.) may not effectively provide excellent friction reduction effects or have low wear resistance in some cases.
[0003] In the field of tribology, metal organic framework materials (MOFs) can adjust the interaction between the friction interface and the lubricating medium through their special pore structure and surface functional groups, thereby achieving the purpose of reducing the friction coefficient and wear rate. In addition, MOFs materials can also improve the mechanical properties of composite materials through cross-linking reactions, and improve toughness and wear resistance. However, traditional MOFs have poor dispersibility in polymer matrices and are prone to agglomeration. This not only affects the effective use of MOFs, but also may lead to a decrease in the mechanical properties of the polymer matrix. The stress dissipation mechanism in the prior art often relies on a single material or structure and lacks a multi-level structural design. This makes it impossible for the material to fully play the role of stress dispersion and energy dissipation when facing a complex friction environment. Therefore, how to achieve efficient dispersion and stability of MOFs in a polymer matrix through structural design, and improve the tribological properties of composite materials through the design of a multi-level stress dissipation layer, is a key issue that needs to be solved urgently. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a polymer-based composite material containing a multi-level MOFs stress dissipation layer, and a preparation method and application thereof. The present invention can introduce MOFs materials such as MXene, Ni-BDC, and ZIF-8 into a polymer matrix, and by constructing a multi-level friction stress dissipation layer, significantly improve the friction and wear resistance, toughness, and durability of the composite material.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a polymer-based composite material containing a multi-level MOFs stress dissipation layer, comprising the following steps:
[0007] The nanocellulose, MXene, Ni-BDC and water are mixed and self-assembled under static conditions to obtain a first mixed slurry;
[0008] Mixing the ZIF-8 nanoparticles and the PVA aqueous solution with the first mixed slurry, and performing a partial hydrolysis reaction under stirring to obtain a second mixed slurry;
[0009] The second mixed slurry is placed in a mold for drying to obtain a polymer-based composite material containing a multi-level MOFs stress dissipation layer.
[0010] Preferably, in parts by mass, the amount of the nanocellulose is 75 to 100 parts, the amount of the MXene is 10 to 25 parts, the amount of the Ni-BDC is 10 to 20 parts, and the amount of the water is 4000 to 5000 parts.
[0011] Preferably, the mixing is one or more of ultrasonic treatment, ball milling treatment, homogenization treatment and mechanical stirring.
[0012] Preferably, the self-assembly reaction time is 24 to 48 hours.
[0013] Preferably, the preparation method of Ni-BDC comprises the following steps:
[0014] NiCl2, 1,4-phthalic acid and N,N-dimethylformamide are mixed and subjected to a solvothermal reaction to obtain Ni-BDC;
[0015] The temperature of the solvent thermal reaction is 100-120° C. and the time is 16-24 hours.
[0016] Preferably, based on the mass fraction of the nanocellulose, the amount of the ZIF-8 nanoparticles is 10 to 20 parts, the amount of the PVA aqueous solution is 3000 to 4000 parts, and the concentration of the PVA aqueous solution is 5 to 7 wt.%.
[0017] Preferably, the partial hydrolysis reaction time is 60 to 180 minutes.
[0018] Preferably, the drying process is carried out at a temperature of 50 to 70° C. and for a time of 14 to 16 hours.
[0019] The present invention provides a polymer-based composite material containing a multi-level MOFs stress dissipation layer prepared by the above preparation method.
[0020] The present invention provides the use of the polymer-based composite material containing a multi-level MOFs stress dissipation layer as a self-lubricating material.
[0021] The invention provides a polymer-based composite material containing a multi-level MOFs stress dissipation layer, comprising the following steps: mixing nanocellulose, MXene, Ni-BDC and water, and performing a self-assembly reaction under static conditions to obtain a first mixed slurry; mixing ZIF-8 nanoparticles and a PVA aqueous solution with the first mixed slurry, and performing a partial hydrolysis reaction under stirring conditions to obtain a second mixed slurry; placing the second mixed slurry in a mold for drying treatment to obtain a polymer-based composite material containing a multi-level MOFs stress dissipation layer.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) Construction of multi-level friction stress dissipation layer: The present invention forms a large-scale hybrid interwoven layer by self-assembling Ni-BDC (nickel-based BDC) and MXene with cellulose, and further hydrolyzes ZIF-8 nanoparticles to form a concave-convex surface with a volcano-like structure. This multi-level stress dissipation layer can effectively disperse the stress generated during the friction process, reduce the accumulation of frictional heat, and thus significantly reduce the wear rate;
[0024] (2) Efficient MOFs dispersion and stability: The present invention confines Ni-BDC and MXene within the cellulose framework through the self-assembly process of the cellulose framework, greatly improving the dispersion and stability of MOFs in the polymer matrix. This structure not only increases the loading capacity of MOFs, but also improves the interfacial bonding between MOFs and the matrix;
[0025] (3) Combination of hydrolysis reaction and cross-linking: The present invention promotes the hydrolysis reaction of ZIF-8 during the stirring process to generate zinc hydroxide, imidazole acid and its derivatives, thereby filling the gaps between the composite matrix and promoting the cross-linking reaction between the stacked layers, thereby further improving the toughness, wear resistance and long-term stability of the composite material;
[0026] (4) Excellent anti-friction and anti-wear properties: The polymer-based composite material prepared by the present invention exhibits excellent self-lubricating ability and extremely low wear rate by constructing a multi-level friction stress dissipation layer on the surface and inside. This enables the material to maintain stable tribological properties during long-term use and prolongs its service life.
[0027] The results of the examples show that the lowest friction coefficient of the polymer-based composite material containing the multi-level MOFs stress dissipation layer prepared by the present invention is 0.015 to 0.037. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a surface morphology of the polymer-based composite material prepared in Example 1;
[0029] Figure 2 This is a surface morphology of the polymer-based composite material prepared in Example 2;
[0030] Figure 3 The friction coefficient curve of the polymer-based composite material prepared in Example 1;
[0031] Figure 4 The friction coefficient curve of the polymer-based composite material prepared in Example 2;
[0032] Figure 5 is a friction coefficient curve of the polymer-based composite material prepared in Example 3;
[0033] Figure 6 The friction coefficient curve of the control group samples prepared in Comparative Examples 1 and 2 is shown. DETAILED DESCRIPTION
[0034] The present invention provides a method for preparing a polymer-based composite material containing a multi-level MOFs stress dissipation layer, comprising the following steps:
[0035] The nanocellulose, MXene, Ni-BDC and water are mixed and self-assembled under static conditions to obtain a first mixed slurry;
[0036] Mixing the ZIF-8 nanoparticles and the PVA aqueous solution with the first mixed slurry, and performing a partial hydrolysis reaction under stirring to obtain a second mixed slurry;
[0037] The second mixed slurry is placed in a mold for drying to obtain a polymer-based composite material containing a multi-level MOFs stress dissipation layer.
[0038] Unless otherwise specified, the raw materials used in the present invention are commercially available.
[0039] In the present invention, nanocellulose, MXene, Ni-BDC and water are mixed and self-assembled under static conditions to obtain a first mixed slurry. In the present invention, the preparation method of Ni-BDC preferably includes the following steps:
[0040] NiCl2, 1,4-phthalic acid and N,N-dimethylformamide are mixed and subjected to a solvothermal reaction to obtain Ni-BDC.
[0041] In terms of mass parts, the amount of NiCl2 is preferably 40 to 50 parts, specifically 40 parts, 45 parts or 50 parts; the amount of 1,4-phthalic acid is preferably 7.5 to 12 parts, specifically 7.5 parts, 10 parts or 12 parts; the amount of N,N-dimethylformamide is preferably 1000 to 1300 parts, specifically 1000 parts, 1200 parts or 1300 parts.
[0042] The present invention has no special requirements for the mixing method, and a mixing method well known in the art can be used. In the present invention, the solvent thermal reaction is preferably carried out in a PTFE reactor, and the temperature of the hydrothermal reaction is preferably 100-120°C, specifically 100°C, 110°C or 120°C. The time of the hydrothermal reaction is preferably 16-24h, specifically 16h, 18h, 20h or 24h. After the hydrothermal reaction, the present invention preferably filters and washes the obtained hydrothermal reaction product to obtain Ni-BDC. In the present invention, the Ni-BDC has a lamellar structure and a size is preferably 10-30μm.
[0043] In the present invention, the amount of the nanocellulose is preferably 75 to 100 parts by mass, specifically 75, 80, 85, 90, 95 or 100 parts. In the present invention, the length of the nanocellulose is preferably 500 to 1000 μm, and the diameter is preferably 20 to 100 nm.
[0044] Based on the mass fraction of the nanocellulose, the amount of the MXene is preferably 10 to 25 parts, specifically 10 parts, 15 parts, 20 parts or 25 parts. In the present invention, the MXene is preferably a multilayer MXene; the lateral size of the MXene is preferably 5 to 30 μm, and the thickness is preferably 5 to 10 μm.
[0045] Based on the mass fraction of the nanocellulose, the amount of the Ni-BDC is preferably 10 to 20 parts, specifically 10 parts, 15 parts or 20 parts.
[0046] Based on the mass fraction of the nanocellulose, the amount of water is preferably 4000 to 5000 parts, specifically 4000 parts, 4500 parts or 5000 parts. In the present invention, the water is preferably distilled water.
[0047] In the present invention, the mixing is preferably strong mixing; in the present invention, the mixing is preferably one or more of ultrasonic treatment, ball milling, homogenization and mechanical stirring. In the present invention, the ultrasonic treatment is preferably cell disruptor ultrasonic treatment, the power of the ultrasonic treatment is preferably 800-1000W, and the time is preferably 60-120min; in the present invention, the speed of the ball milling treatment is preferably 300-400rpm, and the time is preferably 6-10h; in the present invention, the rate of the homogenization treatment is preferably 7000-8000rpm, and the time is preferably 20-30min; in the present invention, the rate of the mechanical stirring is preferably 800-1200rpm, and the time is preferably 18-24h.
[0048] The present invention performs a self-assembly reaction under static conditions. In the present invention, the temperature of the self-assembly reaction is preferably room temperature, and the time is preferably 24 to 48 hours. As a specific embodiment of the present invention, the time of the self-assembly reaction is 24 hours, 36 hours or 48 hours. In the present invention, during the static process, Ni-BDC and MXene self-assemble with cellulose to form a large-sized hybrid interwoven layer, which confines Ni-BDC and MXene within the cellulose framework, which greatly improves the dispersibility and stability of MOFs in the polymer matrix.
[0049] After obtaining the first mixed slurry, the present invention mixes the ZIF-8 nanoparticles and the PVA aqueous solution with the first mixed slurry, and performs a partial hydrolysis reaction under stirring to obtain a second mixed slurry. In the present invention, based on the mass fraction of the nanocellulose, the amount of the ZIF-8 nanoparticles is preferably 10 to 20 parts, specifically 10 parts, 15 parts or 20 parts. In the present invention, the particle size of the ZIF-8 nanoparticles is preferably 100 to 200 nm.
[0050] In the present invention, the molecular weight of the PVA is W Preferably, it is 50000 to 150000, and more preferably 82000. In the present invention, the concentration of the PVA aqueous solution is 5 to 7wt.%, specifically 5wt.%, 6wt.% or 7wt.%. Based on the mass fraction of the nanocellulose, the amount of the PVA aqueous solution is preferably 3000 to 4000 parts, specifically 3000 parts, 3500 parts or 4000 parts. In the present invention, the method for preparing the PVA aqueous solution preferably comprises the following steps:
[0051] The PVA particles are heated and mixed with water to obtain a transparent PVA aqueous solution. In the present invention, the water is preferably distilled water. In the present invention, the temperature of the heating treatment is preferably 96° C., and the time is preferably 6 to 9 hours.
[0052] The present invention performs a partial hydrolysis reaction under stirring. In the present invention, the stirring rate is preferably 800 to 1200 rpm. In the present invention, the temperature of the partial hydrolysis reaction is preferably room temperature, and the time is preferably 60 to 180 min, specifically preferably 60 min, 90 min, 120 min, 150 min or 180 min. In the present invention, the hydrolysis reaction of ZIF-8 is promoted during the stirring process to generate zinc hydroxide, imidazole acid and its derivatives and active species (such as Zn 2+ ), which can fill the gaps between the composite matrix and promote the cross-linking reaction between the stacked layers, further improving the toughness, wear resistance and long-term stability of the composite. Specifically, zinc ions can promote cross-linking by interacting with the hydroxyl groups in PVA, and can also affect the interaction between PVA and nanocellulose. In the cross-linking process of PVA and cellulose, zinc hydroxide (Zn(OH)2) may play a more significant role. There are multiple hydroxyl groups on the cellulose molecular chain, which may react with Zn 2+ The Zn ions form a coordination effect, thereby promoting the cross-linking reaction between PVA and cellulose molecules. 2+ Ions can act as crosslinkers, connecting PVA and cellulose molecules through hydrogen bonds or coordination bonds to form a crosslinked network structure. In addition, imidazole compounds such as imidazole acid mainly enhance the mechanical stability and friction stability of polymer-based composites by improving solubility or enhancing the interaction between molecules through hydrogen bonding.
[0053] After obtaining the second mixed slurry, the present invention places the second mixed slurry in a mold for drying treatment to obtain a polymer-based composite material containing a multi-level MOFs stress dissipation layer. In the present invention, the temperature of the drying treatment is preferably 50-70°C, more preferably 60°C, and the time is preferably 14-16h, specifically 14h, 15h or 16h. In the present invention, the drying treatment can promote the cross-linking effect of the hydrolysis product on the nano-components and the evaporation of water, while promoting the hydrolysis of the polymer surface ZIF-8 and obtaining a polymer-based composite material with a volcano-like structure surface. This volcano-like structure can effectively store the hydrolysis product of ZIF-8 and enable it to participate in the formation of a lubricating transfer film during the friction process and quickly dissipate friction energy. In the present invention, when the drying temperature exceeds 70°C, the performance of the polymer-based composite material will drop sharply.
[0054] The present invention provides a polymer-based composite material containing a multi-level MOFs stress dissipation layer prepared by the above-mentioned preparation method. In the present invention, the polymer-based composite material comprises a polymer matrix and a multi-level MOFs stress dissipation layer dispersed on the surface and inside of the polymer matrix; in the present invention, the polymer matrix is PVA, and the multi-level MOFs stress dissipation layer comprises a hybrid interwoven layer formed by self-assembly of Ni-BDC, MXene and cellulose, and partially hydrolyzed ZIF-8 nanoparticles, and the ZIF-8 nanoparticles are filled in the gap between the hybrid interwoven layer and the polymer matrix.
[0055] The present invention provides the use of the polymer-based composite material containing a multi-level MOFs stress dissipation layer as a self-lubricating material.
[0056] The polymer-based composite material containing a multi-level MOFs stress dissipation layer provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0057] In the following examples, the method for preparing the PVA aqueous solution is to prepare a PVA aqueous solution having a molecular weight of M W = 82000 PVA particles are added into distilled water and heated at 96°C until a transparent solution is obtained, and finally a PVA aqueous solution with a mass fraction of 5 to 7 wt.% is obtained.
[0058] In the following examples, the length of the nanocellulose is 500 to 1000 μm;
[0059] The lateral size of MXene is 5 to 30 μm;
[0060] The particle size of ZIF-8 nanoparticles is 100-200 nm.
[0061] Example 1
[0062] A method for preparing a polymer-based composite material containing a multi-level MOFs stress dissipation layer, comprising the following steps:
[0063] Step 1: After 40 parts of NiCl2·6H2O, 7.5 parts of 1,4-phthalic acid and 1000 parts of N,N-dimethylformamide are mixed evenly, the mixture is transferred into a PTFE reactor and reacted at 100°C for 24 hours, and then washed three times with distilled water and ethanol alternately to obtain Ni-BDC;
[0064] Step 2: 75 parts of nanocellulose are dispersed in 4000 parts of distilled water and 10 parts of MXene and 10 parts of Ni-BDC prepared in step 1 are added, and the mixture is uniformly mixed by mechanical homogenization (8000 rpm, 20 min), and the mixture is further allowed to stand for 24 hours to promote the occurrence of the structural self-assembly process, thereby obtaining a first mixed slurry;
[0065] Step 3: adding 10 parts of ZIF-8 to the first mixed slurry prepared in step 2, and simultaneously adding 3000 parts of a 5 wt.% PVA aqueous solution, and promoting the hydrolysis reaction of part of the ZIF-8 during continuous stirring at room temperature, the stirring rate is 800 rpm, and the time is 180 min, to obtain a second mixed slurry;
[0066] Step 4: Place the evenly stirred second mixed slurry in a mold and dry it at 60°C for 14 hours to promote the cross-linking of the hydrolysis product on the nanocomponents and the evaporation of water, while promoting the hydrolysis of the polymer surface ZIF-8 and obtaining a polymer-based composite material with a volcano-like structure surface.
[0067] Example 2
[0068] A method for preparing a polymer-based composite material containing a multi-level MOFs stress dissipation layer, comprising the following steps:
[0069] Step 1: After 50 parts of NiCl2·6H2O, 12 parts of 1,4-phthalic acid and 1300 parts of N,N-dimethylformamide are mixed evenly, they are transferred into a PTFE reactor and reacted at 120°C for 16 hours, and then washed alternately with distilled water and ethanol three times to obtain Ni-BDC;
[0070] Step 2: 100 parts of nanocellulose are dispersed in 5000 parts of distilled water and 25 parts of MXene and 20 parts of Ni-BDC prepared in step 1 are added, and the mixture is uniformly mixed by mechanical homogenization treatment (7000 rpm, 30 min), and the mixture is further allowed to stand for 48 hours to promote the occurrence of the structural self-assembly process, thereby obtaining a first mixed slurry;
[0071] Step 3: adding 20 parts of ZIF-8 to the first mixed slurry prepared in step 2, and simultaneously adding 4000 parts of 7 wt.% PVA aqueous solution, and promoting the hydrolysis reaction of part of ZIF-8 during continuous stirring at room temperature, the stirring rate is 1000 rpm, and the time is 150 min, to obtain a second mixed slurry;
[0072] Step 4: Place the evenly stirred second mixed slurry in a mold and dry it at 60°C for 16 hours to promote the cross-linking of the hydrolysis product on the nanocomponents and the evaporation of water, while promoting the hydrolysis of the polymer surface ZIF-8 and obtaining a polymer-based composite material with a volcano-like structure surface.
[0073] Example 3
[0074] A method for preparing a polymer-based composite material containing a multi-level MOFs stress dissipation layer, comprising the following steps:
[0075] Step 1: After 45 parts of NiCl2·6H2O, 10 parts of 1,4-phthalic acid and 1200 parts of N,N-dimethylformamide are mixed evenly, the mixture is transferred into a PTFE reactor and reacted at 110°C for 24 hours, and then washed alternately with distilled water and ethanol three times to obtain Ni-BDC;
[0076] Step 2: 90 parts of nanocellulose are dispersed in 4500 parts of distilled water and 15 parts of MXene and 15 parts of Ni-BDC prepared in step 1 are added, and the mixture is uniformly mixed by mechanical homogenization treatment (8000 rpm, 30 min), and the mixture is further allowed to stand for 36 hours to promote the occurrence of the structural self-assembly process, thereby obtaining a first mixed slurry;
[0077] Step 3: adding 15 parts of ZIF-8 to the first mixed slurry prepared in step 2, and simultaneously adding 3500 parts of 6 wt.% PVA aqueous solution, and promoting the hydrolysis reaction of part of ZIF-8 during continuous stirring at room temperature, the stirring rate is 1200 rpm, and the time is 120 min, to obtain a second mixed slurry;
[0078] Step 4: Place the evenly stirred second mixed slurry in a mold and dry it at 60°C for 12 hours to promote the cross-linking of the hydrolysis product on the nanocomponents and the evaporation of water, while promoting the hydrolysis of the polymer surface ZIF-8 and obtaining a polymer-based composite material with a volcano-like structure surface.
[0079] Example 4
[0080] A method for preparing a polymer-based composite material containing a multi-level MOFs stress dissipation layer, comprising the following steps:
[0081] Step 1: After 40 parts of NiCl2·6H2O, 12 parts of 1,4-phthalic acid and 1200 parts of N,N-dimethylformamide are mixed evenly, they are transferred into a PTFE reactor and reacted at 120°C for 18 hours, and then washed three times with distilled water and ethanol alternately to obtain Ni-BDC;
[0082] Step 2: 100 parts of nanocellulose are dispersed in 4000 parts of distilled water and 10 parts of MXene and 20 parts of Ni-BDC prepared in step 1 are added, and the mixture is uniformly mixed by mechanical homogenization (8000 rpm, 30 min), and the mixture is further allowed to stand for 48 hours to promote the occurrence of the structural self-assembly process, thereby obtaining a first mixed slurry;
[0083] Step 3: adding 20 parts of ZIF-8 to the first mixed slurry prepared in step 2, and simultaneously adding 4000 parts of 6 wt.% PVA aqueous solution, and promoting the hydrolysis reaction of part of ZIF-8 during continuous stirring at room temperature, the stirring rate is 1000 rpm, the time is 90 minutes, and a second mixed slurry is obtained;
[0084] Step 4: Place the evenly stirred second mixed slurry in a mold and dry it at 60°C for 14 hours to promote the cross-linking of the hydrolysis product on the nanocomponents and the evaporation of water, while promoting the hydrolysis of the polymer surface ZIF-8 and obtaining a polymer-based composite material with a volcano-like structure surface.
[0085] Comparative Example 1
[0086] Step 1: After 50 parts of NiCl2·6H2O, 12 parts of 1,4-phthalic acid and 1200 parts of N,N-dimethylformamide are mixed evenly, the mixture is transferred into a PTFE reactor and reacted at 120°C for 18 hours, and then washed three times with distilled water and ethanol alternately to obtain Ni-BDC;
[0087] Step 2: 100 parts of nanocellulose are dispersed in 5000 parts of distilled water and 10 parts of Ni-BDC prepared in step 1 are added, and the mixture is uniformly mixed by mechanical homogenization (8000 rpm, 30 min), and the mixture is further allowed to stand for 48 hours to promote the occurrence of the structural self-assembly process, thereby obtaining a first mixed slurry;
[0088] Step 3: adding 10 parts of ZIF-8 to the first mixed slurry prepared in step 2, and simultaneously adding 4000 parts of 6 wt.% PVA aqueous solution, promoting the hydrolysis reaction of part of ZIF-8 during continuous stirring, the stirring rate is 1000 rpm, the time is 60 min, to obtain a second mixed slurry;
[0089] Step 4: Place the evenly stirred second mixed slurry in a mold and dry it in a 60°C environment for 14 hours to promote the cross-linking effect of the hydrolysis product on the nanocomponents and the evaporation of water, while promoting the hydrolysis of the polymer surface ZIF-8 and obtaining a polymer-based composite material, which is recorded as comparison sample 1.
[0090] Comparative Example 2
[0091] Step 1: After 50 parts of NiCl2·6H2O, 12 parts of 1,4-phthalic acid and 1200 parts of N,N-dimethylformamide are mixed evenly, the mixture is transferred into a PTFE reactor and reacted at 120°C for 18 hours, and then washed three times with distilled water and ethanol alternately to obtain Ni-BDC;
[0092] Step 2: 100 parts of nanocellulose are dispersed in 5000 parts of distilled water and 10 parts of Ni-BDC prepared in step 1 are added, and the mixture is uniformly mixed by mechanical homogenization (8000 rpm, 30 min), and the mixture is further allowed to stand for 48 hours to promote the occurrence of the structural self-assembly process, thereby obtaining a first mixed slurry;
[0093] Step 3: adding 4000 parts of 6 wt.% PVA aqueous solution to the first mixed slurry prepared in step 2, and continuously stirring at a rate of 1000 rpm for 120 min to obtain a second mixed slurry;
[0094] Step 4: Place the uniformly stirred second mixed slurry in a mold and dry it in a 60° C. environment for 14 hours to promote the cross-linking effect of the hydrolyzate on the nano-components and the evaporation of water to form a polymer-based composite material, which is recorded as comparative sample 2.
[0095] Structural characterization
[0096] (1) The surface morphology of the polymer-based composite material prepared in Example 1 is shown in FIG. Figure 1 As shown in the figure, it can be seen that it exhibits a concave-convex morphology with alternating distribution of continuous peaks and valleys, which can effectively reduce the actual contact area between the friction pairs during the friction process and enhance the friction reduction and anti-wear properties of the polymer-based composite material. The formation of this peak-like structure is mainly attributed to the hydrolysis reaction of ZIF-8 and its cross-linking effect on the nano-components. Zinc hydrate (such as Zn(H2O)6 2+ ) itself usually does not have strong cross-linking ability, but it may generate some active species (such as Zn 2+ ), these active substances can participate in the cross-linking reaction. Zinc ions can promote cross-linking by interacting with the hydroxyl groups in PVA, and can also affect the interaction between PVA and nanocellulose. In the cross-linking process of PVA and cellulose, zinc hydroxide (Zn(OH)2) may play a more significant role. There are multiple hydroxyl groups on the cellulose molecular chain, which may react with Zn 2+ The Zn ions form a coordination effect, thereby promoting the cross-linking reaction between PVA and cellulose molecules. 2+Ions can act as crosslinkers, connecting PVA and cellulose molecules through hydrogen bonds or coordination bonds to form a crosslinked network structure. In addition, imidazole compounds such as imidazole acid mainly enhance the mechanical stability and friction stability of polymer-based composites by improving solubility or enhancing the interaction between molecules through hydrogen bonding.
[0097] (2) The surface morphology of the polymer-based composite material prepared in Example 2 (partially enlarged area) is shown in FIG. Figure 2 As shown. It can be seen that it exhibits a peak-like structure similar to a crater, showing an inwardly concave structural feature. The reason for the formation of this structure is mainly attributed to the hydrolysis reaction of ZIF-8 during the evaporation of water, which causes the particles to decompose in the peak area and leave a pit-like morphology. This structure can effectively store the hydrolysis products of ZIF-8 and enable it to participate in the formation of a lubricating transfer film during the friction process and quickly dissipate friction energy. It is mainly manifested in the formation of a lubricating film by zinc hydroxide at the friction interface, reducing the friction coefficient and wear, and imidazole acid (or imidazole acid derivatives) may also affect the lubrication performance. Imidazole acid and its derivatives will form a film or coating with strong adhesion on the friction surface, significantly improving the slip of the friction pair at the convex part and promoting the stability of the friction coefficient and the reduction of the wear rate.
[0098] Performance Testing
[0099] (1) The friction coefficient curve of the polymer-based composite material prepared in Example 1 is as follows: Figure 3 As shown. It can be seen that the friction coefficient curve is stable and lasting during the long-term test, and there is almost no running-in period. The final friction coefficient is as low as 0.037. This value has reached an extremely low range in solid self-lubricating materials, indicating that the construction of the multi-level MOFs stress dissipation layer can quickly transfer or transfer the friction stress and friction energy on the surface of the composite material to the inside of the matrix, effectively reducing the friction coefficient of the composite material.
[0100] (2) The friction coefficient curve of the polymer-based composite material prepared in Example 2 is as follows: Figure 4 As shown in the figure, the average friction coefficient is further reduced to an ultra-low value of 0.015, indicating that the multi-level MOFs structure in the polymer matrix has enhanced friction stress transfer energy at high sliding speeds, which enables the friction energy of the friction interface to be transferred to the inside of the matrix at an extremely fast speed through the surface, showing excellent friction energy dissipation capacity.
[0101] (3) The friction coefficient curve of the polymer-based composite material prepared in Example 3 is as follows: Figure 5 It can be seen that the minimum friction coefficient reaches 0.023, which shows that the change of raw material ratio has a certain influence on the friction performance of the composite material, but the fluctuation range of its value is small.
[0102] In summary, the polymer-based composite material containing a multi-level MOFs stress dissipation layer of the present invention exhibits excellent tribological properties: (1) The surface of Ni-BDC may exhibit certain low friction characteristics, and due to its metal center (nickel), it can form a certain chemical adsorption effect with the friction surface, which helps to reduce the friction coefficient; (2) The nanostructure and layered characteristics of MXene enable it to form a thin lubricating film at the friction interface, which helps to reduce the friction coefficient. Its thin sheet structure can slide during the friction process, thereby forming a "lubricating sheet" to further reduce friction; (3) The highly porous structure of ZIF-8 allows it to undergo flexible crystal deformation during the friction process, and significantly improves the dissipation of friction stress through synergy with other materials, greatly reducing the friction coefficient and wear rate of the polymer-based composite material.
[0103] The friction coefficient curves of the control group samples prepared in Comparative Example 1 and Comparative Example 2 are as follows: Figure 6 As shown, the control samples prepared in Comparative Examples 1 and 2 have higher friction coefficients during the friction performance test, and their values reach 0.081 and 0.082 respectively, which are much higher than the composite material containing a stress dissipation layer structure prepared in Example 2 of the present invention. In contrast, the friction coefficient of the control sample without a stress dissipation layer is 446.67% higher than that of the sample in Example 2, indicating that the construction of a multi-level MOFs stress dissipation layer can significantly improve the friction reduction performance of the composite material.
[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a polymer-based composite material containing a multi-level MOFs stress dissipation layer, characterized in that: The following steps are involved: The nanocellulose, MXene, Ni-BDC and water are mixed and self-assembled under static conditions to obtain a first mixed slurry; Mixing the ZIF-8 nanoparticles and the PVA aqueous solution with the first mixed slurry, and performing a partial hydrolysis reaction under stirring to obtain a second mixed slurry; The second mixed slurry is placed in a mold for drying to obtain a polymer-based composite material containing a multi-level MOFs stress dissipation layer.
2. The preparation method according to claim 1, characterized in that: In terms of mass fractions, the amount of the nanocellulose is 75 to 100 parts, the amount of the MXene is 10 to 25 parts, the amount of the Ni-BDC is 10 to 20 parts, and the amount of the water is 4000 to 5000 parts.
3. The preparation method according to claim 1 or 2, characterized in that: The mixing is one or more of ultrasonic treatment, ball milling treatment, homogenization treatment and mechanical stirring.
4. The preparation method according to claim 1 or 2, characterized in that: The self-assembly reaction time is 24 to 48 hours.
5. The preparation method according to claim 1, characterized in that: The preparation method of Ni-BDC comprises the following steps: NiCl2, 1,4-phthalic acid and N,N-dimethylformamide are mixed and subjected to a solvothermal reaction to obtain Ni-BDC; The temperature of the solvent thermal reaction is 100-120° C. and the time is 16-24 hours.
6. The preparation method according to claim 2, characterized in that: Based on the mass fraction of the nanocellulose, the amount of the ZIF-8 nanoparticles is 10 to 20 parts, the amount of the PVA aqueous solution is 3000 to 4000 parts, and the concentration of the PVA aqueous solution is 5 to 7 wt.%.
7. The preparation method according to claim 1, characterized in that: The partial hydrolysis reaction time is 60 to 180 minutes.
8. The preparation method according to claim 1, characterized in that: The drying process is carried out at a temperature of 50 to 70° C. and for a time of 14 to 16 hours.
9. A polymer-based composite material containing a multi-level MOFs stress dissipation layer prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the polymer-based composite material containing a multi-level MOFs stress dissipation layer as claimed in claim 9 as a self-lubricating material.
Citation Information
Patent Citations
Preparation method and application of NiFe-LDH composite material
CN112391649A
Lignocellulose-MXene / polytetrafluoroethylene wax confinement self-lubricating material and preparation method thereof
CN114958466A
ZIF-7 / 2D Ni-BDC nano composite lubricating material and preparation method thereof
CN115386408A
Hybrid composite comprising metal-organic framework (MOF) and two-dimensional sheet
WO2022114714A1